Optimalisasi Kinerja Keuangan UMKM Berbasis Ekonomi Syariah : Perspektif Keberlanjutan Bisnis Ekonomi dan Inovasi Terbuka - Trie Yolanda Sari; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to enhance the financial performance of Micro, Small, and Medium Enterprises (MSMEs) by applying sharia economic principles, with a focus on business sustainability and open innovation. MSMEs are vital to the Indonesian economy but often face challenges such as limited capital, restricted market access, and low sharia financial literacy. Using a sharia economic framework rooted in principles of fairness, transparency, and sustainability, the study explores innovative strategies to boost the competitiveness of MSMEs. The open innovation approach promotes collaboration between MSMEs and various stakeholders, including sharia financial institutions, government agencies, and local communities, to create a supportive environment for sustainable development. The findings suggest that integrating sharia economic principles with open innovation can enhance operational efficiency, strengthen financial structures, and positively impact the long-term sustainability of MSMEs. Based on these results, the study recommends that MSMEs incorporate this approach into their financial management practices to navigate global economic challenges and achieve sustainable growth.